P2X Receptors: Potential Therapeutic Targets for Symptoms Associated With Lung Cancer — A Mini Review - Mai, Yonglin; Guo, Zhihua; Yin, Weiqiang; Zhong, Nanshan; Dicpinigaitis, Peter V.; Chen, Ruchong (Frontiers in Oncology, 2021)
Symptoms associated with lung cancer mainly consist of cancer-associated pain, cough, fatigue, and dyspnea. However, underlying mechanisms of lung cancer symptom clusters remain unclear. There remains a paucity of effective treatment to ameliorate debilitating symptoms and improve the quality of life of lung cancer survivors. Recently, extracellular ATP and its receptors have attracted increasing attention among researchers in the field of oncology. Extracellular ATP in the tumor microenvironment is associated with tumor cell metabolism, proliferation, and metastasis by driving inflammation and neurotransmission via P2 purinergic signaling. Accordingly, ATP gated P2X receptors expressed on tumor cells, immune cells, and neurons play a vital role in modulating tumor development, invasion, progression, and related symptoms. P2 purinergic signaling is involved in the development of different lung cancer-related symptoms. In this review, we summarize recent findings to illustrate the role of P2X receptors in tumor progression and lung cancer- related symptoms, providing an outline of potential anti-neoplastic activity of P2X receptor antagonists. Furthermore, compared with opioids, P2X receptor antagonists appear to be innovative therapeutic interventions for managing cancer symptom clusters with fewer side effects.